Storylines of research on resource extraction and health in Canada: A modified metanarrative synthesis. (May 2021) - Brisbois, Ben; Hoogeveen, Dawn; Allison, Sandra; Cole, Donald; Fyfe, Trina M.; Harder, Henry G.; Parkes, Margot W.
Abstract: Patterns of research on resource extraction's health effects display problematic gaps and underlying assumptions, indicating a need to situate health knowledge production in the context of disciplinary, corporate and neocolonial influences and structures. This paper reports on a modified metanarrative synthesis of 'storylines' of research on resource extraction and health in the Canadian context. Peer-reviewed articles on mining or petroleum extraction and health published between 2000 and 2018 and dealing with Canadian populations or policies (n = 87) were identified through a systematic literature search. Coding identified main disciplinary traditions, methodologies and approaches for judging high-quality research. Underlying assumptions were analyzed in terms of models of health and well-being; resource extraction's political economic drivers; and representations of Indigenous peoples, territories and concerns. Findings included a preponderance of occupational and environmental health studies; frequent presentation of resource extraction without political economic antecedents, and as a major contributor to Canadian society; sustainable development aspirations to mitigate health impacts through voluntary private-sector governance activities; representations of Indigenous peoples and concerns ranging from complete absence to engagement with legacies of historical trauma and environmental dispossession; and indictment of corporate (especially asbestos industry) and government malfeasance in a subset of studies. Canada's world-leading mining sector, petroleum reserves and population health traditions, coupled with colonial legacies in both domestic and overseas mining and petroleum development, make these insights relevant to broader efforts for health equity in relation to resource extraction. They suggest a need for strengthened application of the precautionary principle in relation to resource extraction; nuanced attention to corporate influences on the production of health science; more profound challenges to dominant economic development models; and extension of well-intentioned efforts of researchers and policymakers working within flawed institutions. Highlights: We identified storylines of research on resource extraction and health in Canada. Of 87 included articles, 39 were coded as occupational health & safety. Virtually all articles assumed status-quo economic development trajectories. Corporate-origin narratives were frequently reproduced in health scholarship. Indigenous presence ranged from complete absence to respectful engagement.